Duck! Rabbit! - Rosenthal, Amy Krouse; Lichtenheld, Tom (San Francisco, Calif. : Chronicle Books, 2009)
Two unseen characters argue about whether the creature they are looking at is a rabbit or a duck.
Booklist starred
School Library Journal
Wilson's Children
Booklist starred, April 2009
Horn Book, October 2009
Kirkus Review, March 2009
Keywords: Animals -- Identification -- Juvenile fiction; Animals -- Identification -- Fiction; Animals -- Identification -- Fiction